2013
DOI: 10.1002/ar.22798
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells and Their Subpopulation, Pluripotent Muse Cells, in Basic Research and Regenerative Medicine

Abstract: Mesenchymal stem cells (MSCs) have gained a great deal of attention for regenerative medicine because they can be obtained from easy accessible mesenchymal tissues, such as bone marrow, adipose tissue, and the umbilical cord, and have trophic and immunosuppressive effects to protect tissues. The most outstanding property of MSCs is their potential for differentiation into cells of all three germ layers. MSCs belong to the mesodermal lineage, but they are known to cross boundaries from mesodermal to ectodermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 108 publications
0
35
0
Order By: Relevance
“…The ALDH, used to identify the hematopoietic stem cells, was present at a high level (more than 70%) to passage 4 [93]. In addition, there is a report indicating the expression of CD71 and MHC class I by both ASCs and BM-MSCs [94]. It is worth to note that the data referring to the surface molecule characteristic for ASCs are inconsistent.…”
Section: Adipose Tissue-derived Mesenchymal Stem Cell Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…The ALDH, used to identify the hematopoietic stem cells, was present at a high level (more than 70%) to passage 4 [93]. In addition, there is a report indicating the expression of CD71 and MHC class I by both ASCs and BM-MSCs [94]. It is worth to note that the data referring to the surface molecule characteristic for ASCs are inconsistent.…”
Section: Adipose Tissue-derived Mesenchymal Stem Cell Characteristicsmentioning
confidence: 99%
“…Busser et al [98] have demonstrated the lack of expression of SUSD2 and MSCA-1 by mesenchymal stem cells from adipose tissue in situ, in contrast to MSCs from bone marrow. What is more, BM-MSCs have been shown to be positive for CD22, CD51, CD64a, CD340, and CD349, comparing to ASCs [94]. In turn, the researchers have observed that other marker, CD271, allows to define adipose tissue cell subsets with particular abilities, but only in lipoaspiration samples and not in abdominoplasty samples [98].…”
Section: Adipose Tissue-derived Mesenchymal Stem Cell Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite their common consideration as a ‘mulitpotent’ stem cell population merely capable of differentiating into cell types of mesodermal origin, MSCs have been considered attractive and viable stem cell sources for regenerative medicine due to their accessibility, abundance and lack of tumorigenic propensity [27]. MSCs have been shown to differentiate across all three germ cell lineages with varying efficiencies both in vitro and in vivo , contributing to tissue regeneration and repair in some cases [28].…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%